The ritual of rights in Japan : law, society, and health policy - Feldman, Eric A. (Cambridge studies in law and society., 2000)
The Ritual of Rights in Japan rejects the traditional view that Japan is a nation where overt conflict and the assertion of rights are unacceptable. It examines both historical events and contemporary policy, in concluding that rights-based conflict is an important part of Japanese legal, political, and social practice.